Biological and Chemical Weapons : Criminal Sanctions and Federal Regulations. (U.S. Congressional Research., 2001)
Reviews criminal sanctions under international and domestic law relating to the development, production, possession, and use of biological and chemical weapons, and discusses certain Federal regulations concerning the development, production, and transportation of biological agents.